A systematic review and meta-analysis of studies of reactivity to digital in-the-moment measurement of health behaviour. Issue 4 (2nd October 2022) - König, Laura M.; Allmeta, Anila; Christlein, Nora; Van Emmenis, Miranda; Sutton, Stephen
ABSTRACT: Self-report measures of health behaviour have several limitations including measurement reactivity, i.e., changes in people's behaviour, cognitions or emotions due to taking part in research. This systematic review investigates whether digital in-the-moment measures induce reactivity to a similar extent and why it occurs. Four databases were searched in December 2020. All observational or experimental studies investigating reactivity to digital in-the-moment measurement of a range of health behaviours were included if they were published in English in 2008 or later. Of the 11, 723 records initially screened, 30 publications reporting on 31 studies were included in the qualitative synthesis/ 7 studies in the quantitative synthesis. Eighty-one percent of studies focused on reactivity to the measurement of physical activity indicators; small but meaningful pooled effects were found (Cohen's d s: 0.27–0.30). Only a small number of studies included other behaviours, yielding mixed results. Digital in-the-moment measurement of behaviour thus may be as prone to reactivity as self-reports in questionnaires. Measurement reactivity may be amplified by (1) ease of changing the behaviour (2) awareness of being measured and social desirability, and (3) resolving discrepancies between actual and desired behaviour through self-regulation.